The Relativity of Feminist Legal Theory on Abortion According to Fiqh Dharūrāt - Mumtazi, Fahman; Shalahuddin, Henri; Munawarah, Jannatul (MAHAKIM Journal of Islamic Family Law, 2024)
This study seeks to analyze the epistemological problems from the theories of feminism and their critical point of legalizing abortion from the perspective of sharī'ah through the analysis of fiqh dharūrāt. The method applied is descriptive-analytical with a philosophical approach that aims to analyze the paradigm behind the Dominance Theory, Critical Race Theory, and Postmodernism Theory, which feminists have promoted as the protection of women. The results of this study conclude that dominance theory provides the legality of abortion rights based on the doctrine of the sovereignty of a female’s body without being bounded by morals or other values, including religion. Critical Race Feminist theory used the standard of abortion by considering women's discrimination experiences between white women and black women that create the issue of reproductive health as a form of fulfilling the right of all women's authority to get reproductive health services and determine the future of their bodies. Similarly, postmodern theory explains the legality of abortion rights without being bound by specific moral standards, and the assessment of good and lousy abortion behavior was not left by the justification of society but by the beliefs of the woman. Based on the philosophical basis of the three feminist theories above, the standard of dharūrāt on abortion rights becomes relative and flexible. Fiqh dharūrāt provided the guidance to prevent women from being trapped into relativism so that they could remain in the guidance of revelation and guidance of the sharī'ah.